SISTEM KERJA DAN PRINSIP PASAR MODAL SYARIAH - Parno, Parno (IAIN Samarinda, 2013)
Islamic capital market is the capital market that applies the principles of sharia or the instruments of marketable securities must meet kosher criteria. Prohibition of any transaction that contains elements of usury, maysir, gharar, bay 'najasi, ihtikar. Ban on all investments are not made on the spot, meaning harmony and the terms of the transaction to be complete. Description of the legal basis and principles of capital market transactions above, especially concerning contract forms will provide a way for academics and investors who want to consistently use Islamic principles in assessing the critical instruments of investment instruments available in the capital market . Instruments and transactions that are prohibited in the capital market are preference shares, options, futures, margin trading, short-selling.Instrumen instruments in accordance with sharia is stock (ordinary), Islamic bonds, Islamic mutual funds.